Comparisons of risk factors and outcomes between abdominal aortic aneurysm and peripheral arterial disease: a case-control study - Ian Beeton; Jay Acharya; Bengisu Kesin Meric; James Hobden; Tahir Ali; Thang S. Han (American Journal of Medicine Open)
ABSTRACT: Background: There is a paucity of data on direct comparison of clinical measures in patients with abdominal aortic aneurysm (AAA) and those with peripheral arterial disease (PAD). Here, we examine the risk factors and outcomes between these 2 conditions. Methods: Group differences were examined by Fisher's exact tests with Bonferroni correction, postoperative complications (including delirium and pneumonia) and LOS by logistic regression, and mortality by Cox regression, adjusted for age, sex, smoking, co-morbidities and medications. Results: In total, 160 men and 33 women aged 74.5years (SD = 9.4) were referred for preoperative cardiac assessment for AAA (n = 70) and PAD (n = 123). Vascular surgery was performed in 148 patients (70% of AAA; 80.5% of PAD). Myocardial infarct was more prevalent in AAA, and diabetes more in PAD, whilst atrial fibrillation, stroke, congestive heart failure and hypertension did not differ between groups. Compared to patients with PAD, there were higher proportions of patients with AAA prescribed with cardiovascular medications, and developed post-operative complications in hospital: odds ratio = 7.34 (95% CI, 2.26-23.84, P < .001), and stayed in hospital >1week: odds ratio = 2.60 (95% CI, 1.15-5.85, P = .021). Compared to those with AAA, patients with PAD were at greater risk of death in the entire sample: hazard ratio = 3.34 (95% CI, 1.64-6.79), and in those who underwent vascular surgery: hazard ratio = 4.90 (95% CI, 1.88-12.79). Left ventricular function did not relate to outcomes. Conclusions: Differences between AAA and PAD in risk profile and management which may have a bearing on higher risk of death associated with PAD. More intensive cardiovascular management may help improve their outcomes.